Pola Pembinaan Kepribadian Dalam Perubahan Perilaku Di Lembaga Pembinaan Khusus Anak Kelas I Tangerang - Maulana Arief Farhan; Moh. Amin Tohari (Demokrasi: Jurnal Riset Ilmu Hukum, Sosial dan Politik, 2024)
The purpose of this research is to determine the coaching pattern of the Special Development Institute for Class I Children in Tangerang, to find out the factors that influence changes in children's behavior in dealing with the law, to find out changes in children's behavior in dealing with the law at the Special Development Institute for Class I Children in Tangerang. Children in conflict with the law are children who are in conflict with the law, children who are victims of the law and children who are witnesses to criminal acts. This research uses a qualitative approach with a descriptive approach. Data collection was carried out by observation, interviews and documentation. The number of informants was ten people, including five supervisors of the Class I Special Development Institute for Children in Tangerang and five informants from correctional students. Determining informants using purposive sampling and testing the validity of the data using data triangulation. From the results of this research, it was found that the factors that cause children to encounter the law include social factors, lack of parental supervision, and economic factors. The coaching pattern includes personality coaching. The results of this research include personality development which has a positive impact on changing the behavior of correctional students in institutions in the form of increasing religious skills and increasing knowledge in formal education.